Influence of hydrothermal reaction period of ZnO nanorod arrays on recombination processes in dye sensitized solar cell - Ильясов, Б.Р.; Ибраев, Н.Х. (Recent Contributions to Physics, 2016)
ZnO nanorod arrays were synthetized by hydrothermal deposition technique. Influence of hydrothermal reaction period on specific surface of the nanorod arrays and photovoltaic properties of DSSCs based on ZnO nanorods was studied. Optimal hydrothermal reaction period for growing of ZnO nanorod arrays was determined. It was founded that recombination rate of electrons at ZnO/electrolyte interface and effective diffusion coefficient of electrons in ZnO increase by extending hydrothermal reaction period. Possible explanations of observed phenomena have been offered.